Evaluating the impact of a tablet-based intervention on the mathematics attainment, receptive language and approaches to learning of preschool children - Walton, Jodie M. (2018)
Hand-held technology is increasingly being used in educational settings as a medium of instruction for young children (Hubber et al., 2016). Although the evidence base is developing, little is currently known about the effectiveness of mathematics interventions delivered through tablet technology, particularly for preschool children in the UK. The present research evaluates the impact of the onebillion tablet-based intervention on the mathematics attainment, receptive language and positive ‘approaches to learning’ of 3-4 year old children.